Prevalence, Intensity, and Associated Factors of Schistosoma mansoni among School Children in Northwest Ethiopia - Ayalew Jejaw Zeleke; Ayenew Addisu; Yalewayker Tegegne (Journal of Parasitology Research)
Background. Schistosomiasis is one of the Neglected Tropical Diseases in Ethiopia, and its burden may show variations from time to time across different regions. Thus, this study was aimed at determining the prevalence, intensity, and associated risk factors of Schistosoma mansoni (S. mansoni) among schoolchildren in Northwest Ethiopia. Methods. A school-based cross-sectional study was conducted. A multistage sampling technique was used to select the study participants. Stool specimens were collected and examined using two-slide Kato-Katz method. Data were analyzed using SPSS version 20 software. Multivariate logistic regression analysis was used to identify risk factors. p values less than 0.05 were taken as statistically significant. Result. A total of 786 schoolchildren were participated in this study. The prevalence of S. mansoni was 33.5%. The mean egg count of the parasite among the infected study participants was 523.665 eggs per gram (epg) of stool. Thirty-seven, 42, and 21 percent of the study participant’s infection were due to light, moderate, and heavy infection intensities, respectively. Age of 8-11 years old (AOR=1,687, 95%CI=1.163,2.892), 5th-8th grade level (AOR=2.280, 95%CI=1.348,3.856), residing in Chuahit District (AOR=95.559, 95%CI=12.945,705.419), and using untreated water for domestic supply (AOR=1.724, 95%CI=1.457,2.148) were found to be risk factors for S. mansoni infection. Conclusion. High prevalence of S. mansoni and relatively higher proportion of moderate intensity of infection in this study imply that schistosomiasis is still one of the major public health problems in Northwest Ethiopia. It is also highlighted that study sites, provision of water supply, age, and grade level of the schoolchildren were identified as a risk factors for the disease.